MEWUJUDKAN PEMBELAJARAN ADAPTIF DAN JOYFUL DI MADRASAH IBTIDAIYAH - Dewi, Aura Rahma; Maily, Mulia Eka Wati; Safitri, Frista Nur Cahyani; Zaitunnah, Putri Nor; Mala, Zahrotul Laili; Mahruzah, Nurul Yulia (STKIP Pesisir Selatan, 2025)
The development of digital technology has driven significant transformation in the world of education, including at the Madrasah Ibtidaiyah (MI) level. This article aims to examine the application of adaptive learning and technology-based joyful learning in the MI environment as a strategy to answer the challenges of 21st-century learning. Using a descriptive qualitative approach through a literature study, this article analyzes various literature and best practices relevant to the integration of educational technology. The results of the study indicate that adaptive learning through a digital platform allows for personalization of learning according to individual student needs, while joyful learning based on interactive media increases motivation, participation, and social-emotional development of students. The combination of the two creates a responsive, inclusive, and enjoyable learning environment. Technological innovations such as educational applications, AI-based learning systems, and augmented reality have proven effective in strengthening the learning engagement of MI students. This study concludes that strategic technology integration can strengthen the quality of contextual and globally competitive Islamic basic education.